El impacto de las actividades de extensión universitaria en el área de programación - Hernández Ruiz, Irene (2022)
This paper presents the results obtained in two university extension activities carried out by the project "Creating programming capacities in young people and teachers in both secondary and higher education" of the School of Computer Science of the National University. Scratch day is described, which is a world event that takes place in the month of May to celebrate IDE day and the event “Costa Rica learns with the public U”, an activity where the State University of Costa Rica participated. -AC. In both events, workshops were held where there was the particularity of having a population of different age ranges and from different provinces of the country, but all with a great desire to acquire knowledge in the area activities have had on the participants is reported, for which their perception was known through the use of a web form.